176 Linear and Nonlinear Associations Between Sleep and Academic Achievement in Middle Childhood: The Role of Early Life SES. (3rd May 2021) - Rea-Sandin, Gianna; Breitenstein, Reagan; Doane, Leah; Vakulskas, Emily; Valiente, Carlos; Lemery-Chalfant, Kathryn
Abstract: Introduction: Elementary-aged children in low socioeconomic environments are more likely to experience poor sleep, which can negatively impact academic performance. However, it is unknown whether early-life socioeconomic status (SES) influences associations between sleep and academic achievement later in childhood. Using a demographically diverse sample of children followed longitudinally from 1 to 8 years, we tested linear and nonlinear associations between actigraphy-based sleep duration, midpoint time, sleep duration variability, and parent-reported sleep problems with academic achievement. In addition, we examined whether these associations varied by early SES. Methods: The sample comprised 707 twins (52% female; Mage=8.44 years; 28.7% Hispanic/Latinx; 29.7% at or below the poverty line). SES was ascertained at 1 and 8 years, and children wore actigraph watches to assess sleep for 7 nights (Mnights=6.79) and completed the Applied Math, Picture Vocabulary, and Passage Comprehension subtests of the Woodcock-Johnson IV Tests of Achievement. Primary caregivers also reported on their children's sleep and academic performance (Children's Sleep Habits Questionnaire and Health and Behavior Questionnaire, respectively). Results: Sleep was not linearly related to academic achievement, but there was a significant quadratic association between sleep midpoint with Picture Vocabulary (b=0.28, p<.01) and Passage Comprehension (b=0.17, p<.05). More parent-reported sleep problems were negatively related to Applied Problems performance for lower (b=-1.16, p<.001) and positively associated for higher early SES (b = 1.00, p < .01). More parent-reported sleep problems predicted lower Passage Comprehension for lower (b = -0.59, p < .05), but not higher early SES. Longer sleep duration predicted higher parent-reported academic achievement for lower early SES (b=0.14, p<.01) and lower achievement for higher early SES (b=-0.23, p<.001). Conclusion: Our findings illustrate the complex, sometimes nonlinear associations between children's sleep and academic performance. Many associations varied by early-life SES, suggesting that early childhood environments have long-lasting implications for child functioning, over and above the effect of concurrent SES. Increasing the quantity and quality of children's sleep could improve academic outcomes, particularly for children who have experienced socioeconomic disadvantage. Support (if any): This research was supported by grants from NICHD (R01HD079520 and R01HD086085) and ASU T. Denny Sanford School of Social and Family Dynamics.